2012
DOI: 10.1007/s10822-012-9562-1
|View full text |Cite
|
Sign up to set email alerts
|

Replica exchange Monte-Carlo simulations of helix bundle membrane proteins: rotational parameters of helices

Abstract: We propose a united-residue model of membrane proteins to investigate the structures of helix bundle membrane proteins (HBMPs) using coarse-grained (CG) replica exchange Monte-Carlo (REMC) simulations. To demonstrate the method, it is used to identify the ground state of HBMPs in a CG model, including bacteriorhodopsin (BR), halorhodopsin (HR), and their subdomains. The rotational parameters of transmembrane helices (TMHs) are extracted directly from the simulations, which can be compared with their experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It has been shown that the structures of transmembrane helices are well reproduced in an implicit lipid membrane model by Monte Carlo (MC) simulation [26] and MD simulation [27,28]. Packing of modeled transmembrane helices by the Metropolis MC algorithm accurately predicts the structures of bacteriorhodopsin [29] and halorhodopsin [30]. An important implication of these studies is that the two-stage folding scheme [31] can be used for structure prediction by computational assembly of helical membrane proteins.…”
Section: C1↔o1↔d0↔d1mentioning
confidence: 99%
“…It has been shown that the structures of transmembrane helices are well reproduced in an implicit lipid membrane model by Monte Carlo (MC) simulation [26] and MD simulation [27,28]. Packing of modeled transmembrane helices by the Metropolis MC algorithm accurately predicts the structures of bacteriorhodopsin [29] and halorhodopsin [30]. An important implication of these studies is that the two-stage folding scheme [31] can be used for structure prediction by computational assembly of helical membrane proteins.…”
Section: C1↔o1↔d0↔d1mentioning
confidence: 99%
“…Their clinical importance is demonstrated by the fact that [mt]50% of known drugs in use today target MPs, which are also responsible for the uptake, metabolism, and clearance of these pharmacologically active substances. Despite their biological and pharmaceutical importance, due to difficulties in crystallizing MPs, only about 500 unique structures have been derived so far . As the attempts of using experimental methods to study MPs have encountered difficulties, there exist great incentives for computational and statistical studies of MPs.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the sequence–structure relationship of MPs, we have previously shown that the structure of several MPs, including bacteriorhodopsin, halorhodopsin, and sensory rhodopsin, can be predicted from their sequence using thermodynamic principles . Furthermore, we have combined molecular dynamics simulations and fold identification procedures to predict the structure of 696 kinked and 120 unkinked transmembrane (TM) helices from their sequence in the protein data bank of transmembrane proteins (PDBTM) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have constructed several physical models of TM proteins to predict their three-dimensional structures based on the sequence information [11,12,26]. In these studies, we simplified the folding of TM proteins by the packing of standard helices and predicted their structure by computer simulations.…”
Section: Introductionmentioning
confidence: 99%